2011
DOI: 10.2337/db11-0275
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Curcusomes to Inflammatory Dendritic Cells Inhibits NF-κB and Improves Insulin Resistance in Obese Mice

Abstract: OBJECTIVETo determine whether and by what mechanism systemic delivery of curcumin-containing liposomes improves insulin resistance in the leptin deficient (ob/ob) mouse model of insulin resistance.RESEARCH DESIGN AND METHODSInsulin resistant ob/ob mice with steatosis were injected intraperitoneally with liposome nanoparticles, entrapping the nuclear factor-κB (NF-κB) inhibitor curcumin (curcusomes), and uptake in liver and adipose tissue was determined by flow cytometry. The effects of curcusomes on macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…However, the role of other myeloid cells such as dendritic cells or granulocytes that are target cells of Cre-mediated gene deletion in Atg7 cKO mice 49 cannot be totally eliminated, as both granulocytes and dendritic cells participate in the insulin resistance associated with obesity. 50,51 The development of T2D in Atg7 cKO-ob/ob mice but not in lean Atg7 cKO mice suggests that autophagy-deficient myeloid cells do not display significant inflammatory phenotypes in the basal state, but show proinflammatory features in the presence of activators of inflammation or metabolic stress. Thus, autophagy-deficient Mfs appear to be susceptible to inflammasome activators such as lipids, which is the reason Atg7 cKO mice show increased inflammatory features and overt T2D when they become obese.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of other myeloid cells such as dendritic cells or granulocytes that are target cells of Cre-mediated gene deletion in Atg7 cKO mice 49 cannot be totally eliminated, as both granulocytes and dendritic cells participate in the insulin resistance associated with obesity. 50,51 The development of T2D in Atg7 cKO-ob/ob mice but not in lean Atg7 cKO mice suggests that autophagy-deficient myeloid cells do not display significant inflammatory phenotypes in the basal state, but show proinflammatory features in the presence of activators of inflammation or metabolic stress. Thus, autophagy-deficient Mfs appear to be susceptible to inflammasome activators such as lipids, which is the reason Atg7 cKO mice show increased inflammatory features and overt T2D when they become obese.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings in monocytes from obese subjects, where insulin resistance is associated with increases in oxidative stress and activation of proinflammatory signaling molecules like c-Jun NH (2)-terminal kinase (JNK) and nuclear factor kB inhibitor kinase (IKK-b), indicate that the induction of stress kinase inhibitors such as heat-shock proteins (Hsp) 72 and Hsp27 improves insulin signaling via inhibition of stress kinases and the reduction of serine phosphorylated/inactivated IR substrate 1 (Simar et al 2012). Studies in obese mice have shown that targeting inflammatory dendritic cells improves insulin response resistance through NF-kB (Yekollu et al 2011). However, despite these promising observations, whether insulin resistance treatment or direct pharmacological targeting of inflammation suffices to completely restore the immune response in obese subjects and diabetic patients is still controversial.…”
Section: Insulin Resistance Immune Response Alterations and Cancer:mentioning
confidence: 99%
“…Curcumin liposomes reduced NF-κB and associated inflammatory cytokine production in TNF/iNOS liver dendritic cells and adipose tissue inflammatory macrophages (94).…”
Section: B Vitamin D3 As a Potential Therapeutic Agent For Nafld Trementioning
confidence: 97%
“…As it is highly lipophilic, curcumin bioavailability is also increased when complexed with liposomes, micelles and phospholipids (234). Curcumin liposomes have been shown to be beneficial in treating mice with insulin resistance (94). Curcumin liposomes delivered intraperitoneally to obese mice had reduced systemic insulin resistance as measured by homeostasis model assessment-estimated insulin resistance (HOMA-IR).…”
Section: B Vitamin D3 As a Potential Therapeutic Agent For Nafld Trementioning
confidence: 99%
See 1 more Smart Citation